SISTEM KEAMANAN MOBIL MENGGUNAKAN GLOBAL POSITIONING SYSTEM BERBASIS RASPBERRY PI 3 - Turkhamun Adi Kurniawan; Anie Rahayu (JURNAL SATYA INFORMATIKA, 2020)
The current car security system is still lacking to minimize owner concerns. To anticipate the theft of a car, it requires the addition of a security system that can find out where the location of the car when it was stolen using Global Positioning System (GPS) technology. Through the concept of IoT (Internet of Things) which can support a vehicle movement monitoring system wirelessly integrated using Raspberry Pi as a control system for car security. When a burglar opens the car door by force, the system installs a magnetic sensor as a notification to the owner via Telegram. Cars that have been successfully taken by thieves, the owner can turn off the engine with the help of a Relay on a raspberry pi device.